2016
DOI: 10.1007/s12026-016-8853-3
|View full text |Cite
|
Sign up to set email alerts
|

Irregular antibodies in no hemolytic autoimmune diseases are able to induce erythrophagocytosis

Abstract: Irregular antibodies are produced by alloimmunization because of pregnancies or blood transfusions. They are called "irregular" due to target erythrocyte antigens from "rare blood systems," those different from the ABO system. Irregular antibodies have been widely investigated in immunohematology since their presence in blood donors may lead to difficulties in blood typing and in blood cross-matching, or to induce hemolytic transfusion reactions. Nevertheless, their incidence and participation in the physiopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a large cohort study, alloimmunization was found to be more common in females (2·38%) than males (1·68%, P ≤ 0·0001) [23]. AIHA can be precipitated by previous viral infection and autoimmune diseases, both of which can be associated with loss of immune tolerance [24]. A study of alloantibodies in a cohort of patients with autoimmune disease found that autoantibodies appeared to have IgG and IgM classes of antibodies, suggestive active immune activity, and may cross‐react with similar epitopes in other patients with alloantibodies to Kell and Lutheran [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large cohort study, alloimmunization was found to be more common in females (2·38%) than males (1·68%, P ≤ 0·0001) [23]. AIHA can be precipitated by previous viral infection and autoimmune diseases, both of which can be associated with loss of immune tolerance [24]. A study of alloantibodies in a cohort of patients with autoimmune disease found that autoantibodies appeared to have IgG and IgM classes of antibodies, suggestive active immune activity, and may cross‐react with similar epitopes in other patients with alloantibodies to Kell and Lutheran [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…AIHA can be precipitated by previous viral infection and autoimmune diseases, both of which can be associated with loss of immune tolerance [24]. A study of alloantibodies in a cohort of patients with autoimmune disease found that autoantibodies appeared to have IgG and IgM classes of antibodies, suggestive active immune activity, and may cross‐react with similar epitopes in other patients with alloantibodies to Kell and Lutheran [24,25]. Thus, a hypothesis could be that in patients with a diagnosis of AIHA or suspected AIHA, the PAM approach should be used instead of using PAM for all patients with WAA, given the possibility that the underlying mechanism for WAA alone appears to be tilted towards disease association.…”
Section: Discussionmentioning
confidence: 99%
“…In a presented study, the authors show that these antibodies are widely investigated in immunohematology since their presence in blood donors may lead to difficulties in blood typing and in blood crossmatching, or to induce hemolytic transfusion reactions. They also show that these antibodies do not induce hemolysis in vitro but enhance macrophage-mediated phagocytosis of erythrocytes [11]. Idiopathic hypertrophic pachymeningitis (IHP), characterized by the thickening of cerebral or spinal dura mater, is considered to be of inflammatory origin.…”
Section: Autoantibody Mechanisms Of Actionmentioning
confidence: 99%